Entrepreneurship in the hospitality, tourism and leisure industries - Morrison, Alison J.; Rimmington, Mike.; Williams, Claire; ScienceDirect eBooks (Oxford ; Boston : Butterworth-Heinemann, 1999)
Entrepreneurship is the engine that drives any successful industry or economy. In the rapidly evolving hospitality, tourism and leisure sector worldwide this is particularly true. This new text is designed to develop a greater understanding of the process and context for entrepreneurship as well as to provide key concepts which will enable the reader to become more entrepreneurial themselves. The text unites appropriate theory with copious real world examples giving the student, manager or trainer a powerful framework for understanding every aspect of this vital business function. Rigorously developed by authors with wide teaching and industry experience it contains: *Clear learning objectives and teaching structure *Up-to-date cases throughout *The widest possible coverage of the latest research and literature *A clear focus on the dynamic hospitality, tourism and leisure sector. Entrepreneurship in the Hospitality, Tourism and Leisure Industries is an essential teaching tool and reference on all serious academic and professional courses and gives a uniquely powerful overview of the subject for students and trainees. Up-to-date cases throughout and a major cumulative case running through the text The widest possible coverage of the latest research and literature with a clear focus on the dynamic hospitality, tourism and leisure sector Foreword by Rocco Forte.
The process of entrepreneurship; Entrepreneurs; Corporate entrepreneurship; Environment for enterprise; Finance, business planning and entrepreneurship; Operations and management of entrepreneurial organizations; Marketing and entrepreneurship; Strategy and entrepreneurship; Entrepreneurship, an overview.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Entrepreneurship; Hospitality industry -- Management; Tourism -- Management; Leisure industry -- Management; BUSINESS & ECONOMICS -- Industries -- Hospitality, Travel & Tourism; Entrepreneurship; Hospitality industry -- Management; Leisure industry -- Management; Tourism -- Management; Ondernemerschap; Toeristenindustrie; Entrepreneurship; Freizeitindustrie; Gastgewerbe; Intrapreneuring; Tourismus; Electronic books